Peranan Doa Syafaat Bagi Karya Misi dan Evangelisasi Gereja - Bala, Kristoforus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2016)
The Church, by its very nature, is missionary. The Church is called and sent out by the Most Holy Triune God to proclaim the Good News to all peoples. Evangelization and missionary activities of the early Church were deeply rootedand supported by fervent and constant intercessory prayers of the entire Church. Intercessory prayer was also an integral part of missionary and evangelical activities of Jesus and all his apostles. However, in the modern era, the zeal for evangelization and the spirit of mission of the Church and its missionaries, for some reasons, have been increasingly diminished.The main cause of the problems in mission and evangelization is that there is no committedprayer life.The absence of payer life, in its turn, has caused spiritual dryness, fruitless missionary activities and lack of missionary zeal. Therefore, it is an urgent call for the whole Church and its missionaries to go back to spiritual source, i.e., to take prayer life seriously. All Christians are called to actively and constantly offer intercessory prayers forChurch’s missionary activities and evangelical endeavors. This article describes the meaning of intercessory prayer, characteristics or virtues of a good intercessor, theological foundations of intercessory prayer, intercessors and intercessory prayersboth in the OT and the NT. It will also describe the significance of intercessory prayer in the life of St. Arnold Janssen, the founder of three missionary congregations and some contributions of Catholic Charismatic movement to the life of the Church, especially concerning the increasing awareness of the importance of intercessory prayer and spirit of evangelismin the life of the faithful. And in the last part, it will describe the importance and the urgency of intercessory prayer for mission and evangelization in the eyes of some great Popes.